The Internet show [videorecording] drivers' education for the information superhighway - Byrd, Phillip; Meek, John.; Watts, Bill.; Brandenburg Productions; The Production Companies, Inc. ([S.l.] Brandenburg Productions in association with the Production Companies, Inc., 1994)
Introduces the key to navigating the information superhighway via a clear-cut presentation of the system and a step-by-step guide towards the Internet.
VHS.
Credits : Hosts, John Levine and Gina Smith.
Keywords: Internet (Computer network); File Transfer Protocol (Computer network protocol)